Answer:
x = 2 and x = +2
Step-by-step explanation:
It's essential that you use parentheses to clarify what's happening here:
h(x)=x-4/x^2-4 => h(x)=(x-4) / (x^2-4)
We have vertical asymptotes at x values at which the denominator (x^2 - 4) is zero. That would be x = 2 and x = +2.
d(x) = –9
m(x) = –7x
p(x) = |x|
On the attached diagram you can see all graphs of functions b(x), d(x), m(x) and p(x).
Finding the inverse of a function f(x):
1. First, replace f(x) with y. This is done to make the rest of the process easier.
2. Replace every x with a y and replace every y with an x.
3. Solve the equation from Step 2 for y. This is the step where mistakes are most often made so be careful with this step.
4. Replace y with In other words, you’ve managed to find the inverse.
5. Remember: the domain of f is the range of and the range of f is the domain of .
Using this algorithm, you can find the inverse only in case C:
for m(x)=-7x:
1. y=-7x.
2. x=-7y.
3. y=-x/7.
4. .
5. The domain and the range of m(x) are all real numbers as well as the domain and the range of
Functions b(x) and p(x) are not one-to-one functions (see attached diagram), then you can't find an inverse function. Function d(x) doesn't include x, then you can't also find an inverse function.
3
15
5
10
Answer:
1 and 4
Step-by-step explanation:
All the other options have corresponding x-values
Answer:
The first and fourth options
Step-by-step explanation:
If it's a function no input and have more than one output.
b. 12
c. 15
d. 18
Answer:
b 12
Step-by-step explanation:
1/(9*24)=1/(x*18)
9*24=18x
x=12
Answer:
b. 12 mens are needed to do that job